Turning up the heat: Exploring potential links between climate change and gender-based violence and harassment in the garment sector - Laurel Anderson Hoffner; Joni Simpson; M. Cristina Martinez-Fernandez; Aruch Patumtaewapibal (International Labour Organization (ILO), 2021)
Violence and harassment are widespread issues within the garment sector in Asia, and with the effects of climate change increasing, it is possible that these behaviours could escalate. Using Bangladesh as a case study, this working paper will highlight the intersection between climate change and gender-based violence and harassment by exploring how climate change, measured by increasing heat stress and extreme weather events, could lead to heightened violence being faced by the (mostly female) workers in the sector as a result of its impact on productivity. It is important to note that gender-based violence in the world of work exists independently of climate change; however, evidence finds that violence in the garment sector can be linked to workplace intensity, which is likely to be further stressed by the impacts of climate change, should current trends continue. In addition, gender-based violence tends to increase with higher levels of socio-economic vulnerability, which climate change will also increase. Accordingly, while addressing harmful social norms is key to improving gender equality and reducing gender-based violence and harassment in the world of work, this working paper will explore how climate change will further exacerbate the factors associated with the prevalence of such behaviours within the current context and how, if left unaddressed, this combination of factors could ultimately contribute towards heightened levels of violence and harassment within the garment sector.
Keywords: 330; decent work; clothing and textile industries; partnerships; gender; environment; climate change